A theoretical framework for al-tıb al-nabawi (Prophetic medicine) in modern times - Demirel, Serdar (Kulliyyah of Science, IIUM, 2011)
Al-tıb al-nabaw! means the curative treatments and preventive medicine reported in the Prophetic guidance and practice. The Prophet (s.a.w) applied certain healing practices and advised the use of certain types of food and substances for medical treatments. After the demise of the Prophet (s.a.w), a vast literature had been written in this field. The issue of how to understand the Prophetic medicine has become a subject of interest for Muslims vis-à-vis to others in fields of modern medical sciences. This study aims to analyze al-tıb alnabaw!, paerticularly the theoretical framework of how to explain and understand al-tib al-nabawi in modern times.